2017
DOI: 10.18535/ijahm/v7i4.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Different Culture Medias On Shoot Multiplication And Stigmasterol Content In Accessions Of Centella Asiatica

Abstract: The objective of the study was to assess the effect of three plant tissue culture media (MS, Gamborg's B5 and Nitsch) on the growth of five accessions of Centella asiatica using nodal explant. All the three media supplemented with 1 mg/l BAP resulted in increased growth. Amongst the three Medias, MS media resulted in the highest shoot multiplication in all the five accessions after eight weeks of the incubation period. The highest number of shoots and maximum shoot length were obtained in accession number 3421… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Roy et al [29] also reported that MS media conatins highest number of shoots. In the present study the effect of nitrogen source on shoot multiplication, Murashige and Skoog (MS) [30] (Hi-media) media was prepared and pH was adjusted to 5.8 using 1 N HCl or 1 N NaOH solution.…”
Section: In-vitro Propagation In Different Culture Conditionsmentioning
confidence: 92%
“…Roy et al [29] also reported that MS media conatins highest number of shoots. In the present study the effect of nitrogen source on shoot multiplication, Murashige and Skoog (MS) [30] (Hi-media) media was prepared and pH was adjusted to 5.8 using 1 N HCl or 1 N NaOH solution.…”
Section: In-vitro Propagation In Different Culture Conditionsmentioning
confidence: 92%
“…Several hypothesis has been stated which assume that in high amount of available nutrients, growth predominates and if nutrients are limiting, growth is restricted more than photosynthesis leading to accumulation of fixed carbon which can used up for synthesizing secondary compounds [19][20][21][22][23]. It has been reported that highest shoot multiplication was observed in the MS media compared to Gamborg's B5 media and Nitsch media supplemented with 1 mg/l BAP in five different accession of Centella asiatica [10,12]. The results of all the experimental treatments, shown in terms of mean ± standard error (M ± SE) are statistically analyzed using one-way ANOVA and considered as statistically significant when P ≤ 0.05 and Fstat>Fcritical value.…”
Section: Resultsmentioning
confidence: 99%
“…The most active secondary metabolites of Centella asiatica are triterpene saponin including asiaticoside, madecassoside, asiatic acid, madecassic acids and other valuable terpenoids are brahminoside, thankuniside, sceffoleoside, brahmoside, centellic acid, brahmic acid [7][8][9][10]. Centella asiatica also contains flavanoids like 3 glucosylkaemferol, 7-glucosylkaemferol [11], fatty acids like palmitic, linoleic, stearic, oleic, linolenic acids [2] and also phytosterols like stigmasterol [12]. It is used as wound healing agent and cures various skin diseases including psoriasis, leprosy, eczema due to its potent anti-inflammatory effects and cell proliferative activity and it also possesses antibacterial, antiviral, antifilarial, anti-stress, anti-ulcer, antioxidative stress and anticancer properties [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Centella asiatica belongs to Apiaceae family and found throughout India also in Sri Lanka and Bangladesh. 22 It contains various bioactive compounds which include triterpenes, asiatic acid, asiaticoside, adecassoside, sapogenins, glycosides, madecassic acid, vellarin, and centelloside. 23 Asiatic acid and asiaticoside showed reduce hydrogen peroxide-induced cell death, decline concentration of free radicals, and β-amyloid cell death inhibition in vitro which suggested possible role in Alzheimer's disease treatment and β-amyloid toxicity prevention.…”
Section: Centella Asiatica (Gotu Kola)mentioning
confidence: 99%